Antibacterial and antioxidant properties and phytochemical screening of Laurus nobilis L. extract from Ethiopia - Rebecca Beyene; Aman Dekebo; Teshome Biru (International Journal of Secondary Metabolite)
Microbial resistance to antibiotics and the shortage of efficient antimicrobial agent has necessitated the search for a better antimicrobial agent from various sources. Plants secondary metabolites are the major sources for discovery of new bioactive chemical compounds. The objective of this study was to determine the antibacterial and antioxidant activities of Laurus nobilis leaf extract and its essential oil against human pathogenic microorganisms and to analyse its chemical composition. The leaf of L. nobilis (500 g) was air-dried, powdered and extracted using four different solvents. The crude extract and the essential oil were tested against four Gram-negative and two Gram-positive bacterial strains. The radical scavenging activity of the crud extract was examined using DPPH assay. Bacterial inhibition activity of the crude extract increased with increased concentration from 25 mg/mL to 200 mg/mL. The maximum inhibition zone was recorded against Enterococcus faecalis 13.33±1.52 mm, Escherichia coli 14.33±1.53 mm and Salmonella typhimurium 16.00±1.00 mm, respectively. MeOH extract (1000 µg/mL) showed superior radical scavenging property (0.02) than ascorbic acid (0.05). The analysis of the oil using GC-MS indicated the presence of 48 chemical substances accounting for 91.4 % of the total compositions. The finding of this study showed that bay leaf has considerable antimicrobial and antioxidant activities. Further evaluation of this plant is recommended with particular focus on the mechanisms of action of the antimicrobial substance.